Menanamkan Nilai - nilai Multikultural melalui Permainan Tradisional sebagai Strategi Pendidikan Karakter pada Siswa Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the effectiveness of traditional games as a strategy for instilling multicultural values and character education in elementary school students. Employing a qualitative approach, this research explores the potential of traditional games in shaping attitudes of tolerance, cooperation, and mutual respect for differences among students. The results indicate that traditional games are not only entertainment but also an effective learning medium for instilling positive values and strengthening students' character in the context of cultural diversity.